Dehydrohalogenation of proton responsive complexes: versatile aggregation via pyrazolate pincer ligand arms. Issue 6 (22nd January 2018) - Cook, Brian J.; Chen, Chun-Hsing; Pink, Maren; Caulton, Kenneth G.
Abstract : The behavior of the complex (H2 L)CoCl2, where H2 L is a bis-(pyrazol-3-yl)pyridine, towards Brønsted bases is studied, to evaluate peripheral NH deprotonation as a route to a dianionic pincer ligand on a d 7 center. Abstract : The behavior of the complex (H2 L)CoCl2, where H2 L is a bis-(pyrazol-3-yl)pyridine, towards Brønsted bases is studied, to evaluate peripheral NH deprotonation as a route to a dianionic pincer ligand on a d 7 center. Deprotonation is found to also remove chloride from cobalt, and the decreased metal coordination number is then satisfied by bimolecular reaction of the newly formed peripheral deprotonated pyrazolate nitrogen, leading to Co2 units bridged by some of the pyrazolates, in the analogous species [Co2 (L)(LH)]2 (L) and [Co2 (L)(HL)]2 [Co(L)2 ], but also occasionally by chloride retention, in LiCo2 L2 Cl. Reacting LiCo2 L2 Cl with t BuNC, yields monomeric LCo( t BuNC)2, shown to be a 17 valence electron species. Use of excess LiN(SiMe3 )2 in deprotonation of (H2 L)CoCl2 leads to a product containing a Co[N(SiMe3 )2 ]2 substructure, which illustrates opening of the Co2 L2 dimer in response to an attacking nucleophile.